2008
DOI: 10.1007/s12011-008-8275-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Ferritin Gene Upregulated by Cold Stress in Chorispora bungeana

Abstract: The ability of iron to accept and donate electrons makes it important for plant growth, but it can also damage plants when they are under environmental stress. Ferritin, a protein encoded by the gene Fer, catalyzes the oxidation of Fe(2+) and subsequent storage of Fe(3+) within the mineral core. Ferritin may reduce the adverse effects of iron on Chorispora bungeana Fisch. & C.A. May during the course of cold stress. C. bungeana is a rare alpine subnival plant species that is highly resistant to a freezing envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Notably, an isoform of this family disappeared immediately after the frost episode but reappeared with higher intensity after a week. This result contrasts with other observations that report no effect of cold stress in ferritin expression in pear (Xi et al ) and the upregulation in a cold tolerant alpine plant (Zhang et al ). Whether the disappearance really reflects lack of protein or its modification in such a way that it no longer migrates to the same spot is not clear at this time.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, an isoform of this family disappeared immediately after the frost episode but reappeared with higher intensity after a week. This result contrasts with other observations that report no effect of cold stress in ferritin expression in pear (Xi et al ) and the upregulation in a cold tolerant alpine plant (Zhang et al ). Whether the disappearance really reflects lack of protein or its modification in such a way that it no longer migrates to the same spot is not clear at this time.…”
Section: Discussioncontrasting
confidence: 99%
“…Transcriptome profiling and molecular genetics have analyzed the stress regulatory network of C . bungeana , a subnival alpine plant with inherited cold tolerance [ 33 37 , 39 , 40 ], but little is known about the direct effects of low temperature on epigenetic regulation. Using a combination of the MS-AFLP technique and integrated statistical analyses, we found an interesting variation in DNA methylation of C .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CbFAD3 in C. bungeana was detected using CbACT (AY825362) as the housekeeping gene ( Di et al , 2009 ; Wu et al , 2009 ; Zhang et al , 2009 ). The amplification specificity of each primer pair (P9 and P10 for CbFAD3 , P11 and P12 for CbACT ; Supplementary Table S2 ) was checked by gel electrophoresis and dissolution curve analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Being closely related to Arabidopsis ( Zhao et al , 2012 ), C. bungeana is good plant material for the study of abiotic stress. Previous studies have confirmed that certain physiological and molecular mechanisms, rather than the existence of special morphological characteristics, might contribute towards its high survival under severe environmental conditions ( Fu et al , 2006 ; Zhang et al , 2006 ; Shi et al , 2008 ; Di et al , 2009 ; Wu et al , 2009 ; Zhang et al , 2009 ; Zhao et al , 2012 ). Moreover, we found that the cold tolerance of C. bungeana suspension-cultured cells was associated with the rapid increase in C18:3 under low temperatures ( Shi et al , 2008 ), which was produced mainly by microsomal ω-3 FAD.…”
Section: Introductionmentioning
confidence: 96%